Sustainable Marketing Strategy: Building Brand Image And Customer Loyalty In The Eco-Friendly Era - Ian Zulfikar (Jurnal Ekonomi, 2024)
In the context of modern business competition, demands on companies to implement environmentally friendly practices are increasing, both from the consumer and regulatory side. This study aims to develop sustainable marketing strategies to improve brand image and customer loyalty in the environmentally friendly era. This research uses a qualitative approach with descriptive methods. The research results show that sustainable marketing helps companies build a positive brand image and increase customer loyalty by integrating social and environmental responsibility into marketing strategies. This approach attracts consumers who care about sustainability issues, creates deep emotional connections, and increases trust. Loyal customers tend to make repeat purchases, recommend products to others, and are more tolerant of potential problems. Sustainability is now an important aspect of marketing strategy, where companies that adopt it not only help protect the environment, but also build a positive image and customer loyalty. Steps such as adopting environmentally friendly practices, communicating efforts transparently, and ensuring the environmental impact of products is as small as possible are essential. Sustainability certification and standards also provide official recognition of a company's commitment. By integrating sustainability into all aspects of operations, companies not only gain customer trust, but also contribute to global sustainability goals, making it a must for business continuity and growth.